Foreign Studies Teacher's Guide - Hantula, James; University of Northern Iowa, Cedar Falls ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
Foreign Studies, an elective course for junior and senior students, is a study of selected Asian cultures, including the nations of China, Japan, and India, and of African cultures, including the nations of Nigeria, Ethiopia, and the Democratic Republic of the Congo. Asia and Africa are studied from the American cultural viewpoint with emphasis upon the three concepts of culture, ideology, and the comparison of traditional and modern society. This teacher's guide is divided into four main sections. 1) An outline of content is presented from which many generalizations are developed. These generalizations provide the framework for the development of major cultural understandings. 2) Specific instructional objectives, defined in behavioral terms, are suggested and identified as expected student learnings. These objectives are keyed to skills which are extended in foreign studies. 3) Ninety lesson plans are given, each including a statement of teacher objectives, several teaching techniques, a content outline, comments, and a citation of instructional materials. 4) A bibliography of student and teacher materials is provided. (Author/SJM)
Sponsoring Agency: Ford Foundation, New York, NY.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: African Culture; African History; Area Studies; Asian History; Black Studies; Chinese Culture; Concept Teaching; Cross Cultural Studies; Cultural Awareness; Cultural Differences; Developing Nations; Foreign Countries; Foreign Culture; Non Western Civilization; Secondary Education; Social Studies; Teaching Guides; Intercultural Studies Project